Axillary shoot growth performance from different explants, varieties, culture media, and subculture methods for in vitro culture of Chrysanthemum morifolium - Winarto, Budi; Supriyo, Agus; Beti, Jajuk Aneka; Sudarto; Hindarwati, Yulis; Jauhari, Sodiq; Susila, Arif; Pramono, Joko (Ornamental Horticulture, 2025)
Chrysanthemum morifolium is a commercial cut flower propagated using root suckers and cuttings. In conventional methods, the suckers and cuttings that usually produce low quantity and quality planting materials, can be improved significantly using tissue culture method for achieving varied purposes. The main objective of the research was to reveal different effects of explants, varieties, culture media, and subculture methods on axillary shoot growth performances from initiation to acclimatization. Field-grown shoot tips, thirds, and fifth nodes; ‘Cat Eye’, and ‘Pink Fiji’; initiation, enhancement, and proliferation media; random-cluster subculture methods; direct cutting of shoot tip and node for acclimatization were investigated. Shoot tips of ‘Pink Fiji’ cultured on MS medium containing 2.0 mg L-1 BAP and 0.2 mg L-1 NAA produced high axillary shoots and reduced thereafter due to lowering BAP and NAA. Reducing plant growth regulator (PGR) concentration decreased axillary shoots, but it improved the axillary shoot performances. In the fourth subculture, lowering data in all variables occurred due to substituting sucrose and gelrite to local sugar and agar. Full strength MS medium induced better axillary shoot growth than others in the proliferation stage. Yellowing leaves, decreasing shoot height, and leaf number were noted on ‘Cat Eye’ at fifth subculture, and ‘Pink Fiji’ at seventh subculture. High acclimatized plants derived from shoot tips of ‘Pink Fiji’ with 86% and 83% of nodes were determined on a mixture of burned rice husk, hyacinth manure, and cocopeat (1:1:1, v/v/v). Direct cutting increased the number of the qualified planting materials up to 3 – 5 folds compared to traditional method. Application of the findings can increase quantity and quality planting materials leading to high product selling prices and seed breeder incomes commercially.